DEVELOPMENT STRATEGY OF HOME PALM SUGAR INDUSTRY FROM A MASLAHAH REVIEW (CASE STUDY: BU ATIK'S PALM SUGAR IN KUALUH SELATAN DISTRICT, LABURA REGENCY) - Dewita, Tiara Ajeng; Ramadhani, Sri; Harahap, Muhammad Ikhsan (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study aims to analyze the development strategy of the palm sugar home industry owned by Mrs. Atik in Bandar Lama Village, Kualuh Selatan Subdistrict, Labuhanbatu Utara Regency, using the SWOT approach and the Islamic economic concept of maslahah. The business has been passed down through generations and serves as the family's primary source of income. The research employed interview methods with the business owner and field observations as data collection techniques. SWOT analysis indicates strengths in product quality, producer experience, and low production costs, while weaknesses include limited technology, resources, and lack of brand identity. External opportunities such as rising demand and palm sugar prices offer significant potential, but are challenged by competition, government regulations, and weather dependency. The proposed strategy focuses on leveraging strengths to capture opportunities and addressing internal weaknesses. From the maslahah perspective, development efforts cover the preservation of life, wealth, and lineage (dharuriyah), economic ease (hajiyah), and improvement of quality, morality, and social aspects (tahsiniyah). This research recommends technological upgrades, brand development, human resource training, and the integration of Islamic values to achieve holistic societal benefits. Keywords : Development Strategy, Home Industry, Palm Sugar, SWOT Analysis, Maslahah